Radioimmunszintigraphie mit SPECT: Methodik, Probleme und klinische Erfahrungen - Bares, R.; Fass, J.; Truong, S.; Büll, U.; Schumpelick, V. (Nuklearmedizin - NuclearMedicine, 1987)
Radioimmunoscintigraphy (RIS) with 111ln- and 131 I-labelled monoclonal anti bodies (MAbs) against CEA and/or CA 19-9 was performed in 83 patients with various gastrointestinal carcinomas. A total of 276 body regions could be examined. The results of planar scintigraphy and SPECT were compared intraindividually. Using 111 In-labelled MAbs the sensitivity of RIS was significantly improved by SPECT (88.9 vs. 52.4% with planar scintigraphy, p <0.01). For131 l-labelled MAbs the effect was smaller (83.9 vs. 65.6% with planar scintigraphy, n.s.). This finding can be explained by different kinetics and biodistribution of the used MAb preparations.111 In-labelled MAbs with long whole-body retention and rapid blood clearance reveal ideal qualities for SPECT; on the other hand, the short whole-body retention of131 l-labelled MAbs leads to small count rates and therefore long counting times that make delayed SPECT unsuitable in clinical practice